Sharia Bank Credit Management In Entrepreneurship - Sutikno, Sutikno; Suhaemi, Muhamad; Irsad Ariffin, Muhammad (Universitas Serang Raya, 2022)
The provision of credit for entrepreneurs is currently a separate issue for Islamic banks because they have a small market segment. How to manage Islamic bank credit to expand the market for entrepreneurs in accordance with government policies in supporting the current recovery. For this reason, banks need to manage existing credit so that avoid the risk of bad credit that will arise in the future. For credit management for bank entrepreneurs, it should look at the income generated by business actors per year, in addition to the type of business that has a high level of buyer interest, the bank must pay attention to it. can find out the level of credit risk that exists so that it provides behavior to existing entrepreneurs.